INVESTIGATING THE IMPACT OF INFORMATION TECHNOLOGY IN IMPROVING THE PERFORMANCE OF HUMAN RESOURCES IN ORGANIZATIONS - Zeynab Shirmohamadali (Journal of Population Therapeutics and Clinical Pharmacology, 2023)
The article discusses the importance of skilled human resources in the information technology sector for organizations and countries. It explains how virtual education using information and communication technology is essential for human resource development and management. The impact of information technology on human resource management is also discussed, including productivity, technology training, and future mechanisms. The article concludes that organizations need to adapt to new conditions and utilize information technology to improve human resource management and overall performance.